PENGARUH MODEL PEMBELAJARAN PBL TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMA PADA MATERI IKATAN KIMIA - Roy Efendi Hulu; Saronom Silaban (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to investigate the effect of implementing the Problem Based Learning (PBL) model on students’ motivation and learning outcomes in chemistry, specifically on the topic of Chemical Bonding. The research was conducted at SMA Negeri 4 Medan using an experimental design with two classes: class X-4 as the experimental group taught with PBL, and class X-7 as the control group taught with conventional methods. Data were collected through pre-tests, post-tests, and motivation questionnaires. The findings revealed that the average motivation score of students in the experimental group (79.78) was higher than that of the control group (58.06). Similarly, the average learning outcome score in the experimental group (85.28) was higher than in the control group (65.83). Hypothesis testing confirmed that PBL significantly influenced both motivation and learning outcomes. Furthermore, a strong positive correlation (r = 0.891) was found between students’ motivation and their learning outcomes. These results indicate that the Problem Based Learning model is effective in enhancing students’ motivation and achievement in chemistry learning, particularly in the topic of Chemical Bonding. Keywords: Problem Based Learning, Learning Motivation, Learning Outcomes, Chemical Bonding, High School   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model Problem Based Learning (PBL) terhadap motivasi dan hasil belajar siswa SMA pada materi Ikatan Kimia. Penelitian dilaksanakan di SMA Negeri 4 Medan dengan menggunakan desain eksperimen pada dua kelas, yaitu kelas X-4 sebagai kelas eksperimen yang diajar dengan model PBL dan kelas X-7 sebagai kelas kontrol yang diajar dengan metode konvensional. Data dikumpulkan melalui pre-test, post-test, serta angket motivasi belajar. Hasil penelitian menunjukkan bahwa rata-rata motivasi belajar siswa pada kelas eksperimen (79,78) lebih tinggi dibandingkan kelas kontrol (58,06). Demikian pula, rata-rata hasil belajar siswa pada kelas eksperimen (85,28) lebih tinggi dibandingkan kelas kontrol (65,83). Uji hipotesis menunjukkan bahwa model PBL berpengaruh signifikan terhadap motivasi dan hasil belajar siswa. Selain itu, terdapat korelasi positif yang sangat tinggi (r = 0,891) antara motivasi belajar dan hasil belajar siswa. Dengan demikian, penerapan model Problem Based Learning terbukti efektif dalam meningkatkan motivasi serta hasil belajar siswa pada materi Ikatan Kimia. Kata kunci: Problem Based Learning, Motivasi Belajar, Hasil Belajar, Ikatan Kimia, SMA